Modulation of amygdala reactivity following rapidly acting interventions for major depression. Issue 7 (1st March 2020) - Loureiro, Joana R. A.; Leaver, Amber; Vasavada, Megha; Sahib, Ashish K.; Kubicki, Antoni; Joshi, Shantanu; Woods, Roger P.; Wade, Benjamin; Congdon, Eliza; Espinoza, Randall; Narr, Katherine L.
Abstract: Electroconvulsive therapy (ECT) and ketamine treatment both induce rapidly acting antidepressant effects in patients with major depressive disorder unresponsive to standard treatments, yet their specific impact on emotion processing is unknown. Here, we examined the neural underpinnings of emotion processing within and across patients ( N = 44) receiving either ECT ( N = 17, mean age: 36.8, 11.0 SD ) or repeated subanesthetic (0.5 mg/kg) intravenous ketamine therapy ( N = 27, mean age: 37.3, 10.8 SD ) using a naturalistic study design. MRI and clinical data were collected before (TP1) and after treatment (TP2); healthy controls ( N = 31, mean age: 34.5, 13.5 SD ) completed one MRI session (TP1). An fMRI face‐matching task probed negative‐ and positive‐valence systems. Whole‐brain analysis, comparing neurofunctional changes within and across treatment groups, targeted brain regions involved in emotional facial processing, and included regions‐of‐interest analysis of amygdala responsivity. Main findings revealed a decrease in amygdalar reactivity after both ECT and ketamine for positive and negative emotional face processing ( p < .05 family wise‐error (FWE) corrected). Subthreshold changes were observed between treatments within the dorsolateral prefrontal cortex and insula ( p < .005, uncorrected). BOLD change for positive faces in the inferior parietal cortex significantly correlated with overall symptom improvement, and BOLD change in frontal regions correlated with anxiety for negative faces, and anhedonia for positive faces ( p < .05 FWE corrected). Both serial ketamine and ECT treatment modulate amygdala response, while more subtle treatment‐specific changes occur in the larger functional network. Findings point to both common and differential mechanistic upstream systems‐level effects relating to fast‐acting antidepressant response, and symptoms of anxiety and anhedonia, for the processing of emotionally valenced stimuli.